The Role of Situa-Tua in Divorce Mediation: A Study of Customary Dispute Resolution in Desa Karing, Kecamatan Berampu, Kabupaten Dairi - Nasution, Rakha Dzaky Irvi; Syahputra, Akmaluddin (Al-Risalah, 2025)
This study examines the role of Situa-Tua in mediating divorce cases in Desa Karing, Kecamatan Berampu, Kabupaten Dairi, with a focus on customary and religious approaches. The research aims to analyze the effectiveness of Situa-Tua in reducing divorce rates and resolving marital disputes outside the formal judicial system. Using a qualitative approach, this study employs in-depth interviews with Situa-Tua, religious leaders, and community members, as well as direct observation of the mediation process. The data were analyzed using an interpretive method to understand the strategies and challenges faced by Situa-Tua in handling divorce cases. The findings indicate that Situa-Tua primarily mediate through spiritual counseling and family involvement, following the principles outlined in Q.S. An-Nisa: 35. Their approach emphasizes privacy, cost efficiency, and reconciliation, making it a preferred alternative to litigation. However, the success of mediation depends on the willingness of both parties to cooperate and adhere to religious and customary values. This study contributes to the existing literature by highlighting the integration of customary and Islamic mediation practices in divorce resolution. Unlike formal legal proceedings, Situa-Tua mediation fosters a communal approach to dispute resolution, reinforcing local traditions and religious teachings. The findings suggest that strengthening non-litigation mediation mechanisms, particularly those rooted in local wisdom, can enhance social harmony and reduce the burden on religious courts. Future studies should explore the applicability of this model in other cultural contexts.